5-Hydroxyethyl-3-tetradecanoyltetramic acid represents a novel treatment for intravascular catheter infections due to Staphylococcus aureus - Zapotoczna, Marta; Murray, Ewan J.; Hogan, Siobhan; O'Gara, James P.; Chhabra, Siri Ram; Chan, Weng C.; O'Neill, Eoghan; Williams, Paul (Oxford University Press, 2016)
Objectives: Biofilm infections of intravascular catheters caused by Staphylococcus aureus may be treated with catheter lock solutions (CLSs). Here we investigated the antibacterial activity, cytotoxicity and CLS potential of 5-hydroxyethyl-3-tetradecanoyltetramic acid (5HE-C14-TMA) compared with the related compounds 3-tetradecanoyltetronic (C14-TOA) and 3-tetradecanoylthiotetronic (C14-TTA), which are variants of quorum sensing signalling molecules produced by Pseudomonas aeruginosa.